Macromedia dreamweaver MX 2004 : training from the source. - Page, Khristine Annwn, ....- (Berkeley : Macromedia, 2004)
Learning is doing--which means you're guaranteed to expand your skill set exponentially as you work your way through the 18 project-based tutorials that form the core of this volume on Macromedia's Dreamweaver MX 2004. With its powerful combination of visual layout tools, application development features, and code editing support, Dreamweaver MX 2004 really is a Web designer's dream, and Macromedia's official guide shows you how to transform your dream projects into real-life success stories by creating and maintaining Web sites in an environment that integrates both visual editing and code editing. By re-creating the book's sample Web site, you'll learn the skills and techniques necessary to create your own widely accessible sites. In addition to the basics of creating a Web page that incorporates text, graphics and tables, you'll learn about all that's new in Dreamweaver MX 2004: dynamic cross-browser validation, improved CSS support, built-in graphics editing, and more. The companion CD-ROM contains all of the lesson files as well as a free trial version of Dreamweaver MX 2004.
Keywords: Elektronisch publiceren; Programmatuurontwikkeling; Www world wide web